Current Insights Into the Maintenance of Structure and Function of Intervertebral Disc: A Review of the Regulatory Role of Growth and Differentiation Factor-5 - Bin Lv; Weikang Gan; Zhangrong Cheng; Juntao Wu; Yuhang Chen; Kangchen Zhao; Yukun Zhang (Frontiers Media S.A., 2022)
Intervertebral disc degeneration (IDD), characterized by conversion of genotypic and phenotypic, is a major etiology of low back pain and disability. In general, this process starts with alteration of metabolic homeostasis leading to ongoing inflammatory process, extracellular matrix degradation and fibrosis, diminished tissue hydration, and impaired structural and mechanical functionality. During the past decades, extensive studies have focused on elucidating the molecular mechanisms of degeneration and shed light on the protective roles of various factors that may have the ability to halt and even reverse the IDD. Mutations of GDF-5 are associated with several human and animal diseases that are characterized by skeletal deformity such as short digits and short limbs. Growth and differentiation factor-5 (GDF-5) has been shown to be a promise biological therapy for IDD. Substantial literature has revealed that GDF-5 can decelerate the progression of IDD on the molecular, cellular, and organ level by altering prolonged imbalance between anabolism and catabolism. GDF family members are the central signaling moleculars in homeostasis of IVD and upregulation of their gene promotes the expression of healthy nucleus pulposus (NP) cell marker genes. In addition, GDF signaling is able to induce mesenchymal stem cells (MSCs) to differentiate into NPCs and mobilize resident cell populations as chemotactic signals. This review will discuss the promising critical role of GDF-5 in maintenance of structure and function of IVDs, and its therapeutic role in IDD endogenous repair.